KARAKTERISTIK SUARA KELOMPOK KODOK MICROHYLIDAE BERTUBUH KECIL ASDAL BALI (ANURA: MICROHYLIDAE) - Kurniati, Hellen; Hamidy, Amir (JURNAL BIOLOGI INDONESIA, 2014)
Advertisement calls of Microhyla palmipes and Oreophryne monticola have never been described before; howevercharacteristics of M. orientalisâ??s calls has been described just to support new species publication. The advertisement calls oftwo individual males of M. orientalis and M. palmipes which originated from Wongaya Gede, Bali were recorded in July2010 at air temperatures of 26.0Â°C. Three individuals males of O. monticola were recorded in Eka Karya Botanical Garden,Bali at air temperature of 25.0Â°C. Call components were obtained from 65 calls of M. orientalis, consisting of 95 pulses; 10calls of M. palmipes, consisting of 113 pulses; 3 calls of O. monticola, consisting of 127 pulses, which were then analyzed toobtain the characteristics of sound waves by using software of Adobe Audition 3.0. Sound waves of M. orientalis mainlyconsists of two dominant frequencies raging from 1873-2062 Hz and 3375-3562 Hz; however sound waves of M. palmipesand O. monticola mainly consist of only one dominant frequency that ranges of the frequency is the same, i.e. 3000-3937Hz. Although M. palmipes and O. monticola have the same range on dominant frequency, but the two species have significantlydifferent on number of period per pulse, pulse duration, pulse interval, pulse period, call duration and call interval.Key words: frog call, Microhylidae, Bali Island